A web-based comprehensive head and neck cancer patient education and support needs program: Usability testing. (9th March 2022) - Jabbour, Joe; Dhillon, Haryana M; Shepherd, Heather L; Sundaresan, Puma; Milross, Chris; Clark, Jonathan R
Background: With increasing accessibility of the World Wide Web, patients are using it to obtain patient education materials (PEM). With this in mind, our group (surgeons, radiation oncologists, medical oncologists, nursing, allied health professionals and academic researchers) developed a comprehensive information resource for patients with head and neck cancer (HNC), the Head and Neck Cancer Australia, formerly Beyond Five website. The aim of this study was to determine patient usability of the Head and Neck Cancer Australia website.Methods: Usability testing (Cognitive walkthrough & Think-Aloud) in 18 patients treated for HNC was undertaken at a Cancer centre (anonymous for reviewers).Results: The tasks rated easiest by patients were finding information on psychological well-being (mean time spent: 66 s, range: 10–565), health and well-being effecting quality of life (mean time spent: 36 s, range 9–117) and carer information (mean time spent: 10 s, range 3–35). Patients indicated the website contained a lot of information, covers most topics, was a trusted source of information and a springboard to other information.Conclusions: The Head and Neck Cancer Australia website provides a wide range of information and support in multiple formats available to HNC patients. Further refinements in design, navigation and website instructions are needed to allow effective patient interaction.